Poglądy św. Augustyna w kwestii możliwości zawarcia powtórnego małżeństwa - Dzierżon, Ginter (Ius Matrimoniale, 2017)
The author of the presented article focused his attention on the subject of the views of Saint Augustine on the question of the possibility of remarriage. His analyses show that the bishop of Hippo stood heavily against enabling people to remarry, even in the case of adultery by one of the parties. Such an opinion resulted from the principle assumptions of the bishop’s theory of marriage, especially concerning sacramentality, marital fidelity and indissolubility of marriage. Saint Augustine strongly opposed the solutions adopted in the Roman law which allowed remarriage. Against the laws of this legal order which justified immoral deeds of a man while not justifying such deeds of a woman, he stood clearly for equality of husband and wife in this matter. Therefore, he was definitely against remarriage.